Central America: The Value of International Academic Cooperation - Svenson, Nanette (International Higher Education, 2013)
This article reviews the state of scientific research and development in Central America and emphasizes the contribution of international academic cooperation. Challenges to developing scientific and technological capacity in the region include educational quality and completion rates, inadequate research funding, minimal institutionalization and language barriers. Certain collaborative cross-border university- and research institute-led initiatives are beginning to counter these obstacles and produce significant results. These programs offer hopeful models for Central America and other developing regions.